Peningkatan Hasil Belajar Biologi Siswa Kelas XI IPA SMA Negeri 1 Ajangloe Kabupaten Bone Melalui Model Pembelajaran ATI - Asia, Muhammadiyah; Syamsu, Rijal (Fakultas MIPA UNM, 2010)
This research aims to identify improvement of biological learning achievement through the application of ATI (Aptitude, Treatment, Interaction) learning model on students of Class XI Science 3 SMA 1 Ajangale Bone. This research is packaged in classroom action research conducted in cycle repeats. Each cycle consisted of planning, action, observation, reflection and replanning. Data collected through learning achievement test which given after first and second cycle, and then analyzed by descriptive statistics quantitative. The results showed that implementation of the ATI (Aptitude, Treatment, Interaction) learning model can improve biological learning achievement of the student of Class XI Science 3 SMA 1 Ajangale Bone.